Human Welfare And Environment In Sub-Saharan Africa: The Moderating Role Of Human Capital Development And Institutional Quality - Amoaning Felix (University of Cape Coast)
Human capital development and institutional quality are crucial in human interactions with the environment. As economic agents consume environmental resources to fuel prosperity, their actions release emissions which are gradually eroding the environment's ability to support sustainable progress. To derive benefits for human welfare through environmental resource consumption and reduce the impending ecological risks, this study addresses three objectives using data spanning 2004 to 2019 across 32 sub-Saharan African countries: a) investigate the role of human capital development on the impact of natural resource rents on human welfare; b) analyze the impact of institutional quality on environmental degradation; and c) assess the effect of institutional quality on the turning point of the welfare-environment relationship. Employing an array of econometric techniques, including the system GMM, Hansen fixed-effect threshold model and Driscoll and Kraay standard errors, the estimations confirmed the natural resource curse hypothesis. However, with a threshold level of human capital and higher education enrollment above 2.4 units and 23.21 percent, the dumping effect of natural resource dependence on human welfare progress may be averted. Again, the study reveals that most SSA countries are at the early stage of the EKC and welfare-enhancing activities heighten pollution. However, enhanced rule of law, governance and regulations efficacy not only contribute to emissions abatement in the presence of efforts to enhance human progress but also help bring down the critical level of human welfare at which the relationship between human progress and pollution turns negative. To offset the resource curse, the study recommends that governments and finance ministries prioritize investments in the education sector to boost enrollment and human capital development. Non-resource-rich nations need to increase tertiary school enrollment to at least 25.20 percent to maximize benefits from natural resources. Lastly, endeavours to elevate human progress must be accompanied by robust governance, effective regulations and the establishment of strong legal frameworks.
xvii,305p:,ill
Keywords: Human welfare Environment Natural resource rents Human capital development Institutional quality